2017
DOI: 10.1371/journal.pmed.1002303
|View full text |Cite
|
Sign up to set email alerts
|

Measuring personal beliefs and perceived norms about intimate partner violence: Population-based survey experiment in rural Uganda

Abstract: BackgroundDemographic and Health Surveys (DHS) conducted throughout sub-Saharan Africa indicate there is widespread acceptance of intimate partner violence, contributing to an adverse health risk environment for women. While qualitative studies suggest important limitations in the accuracy of the DHS methods used to elicit attitudes toward intimate partner violence, to date there has been little experimental evidence from sub-Saharan Africa that can be brought to bear on this issue.Methods and findingsWe embed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 74 publications
1
35
0
Order By: Relevance
“…However, the two constructs have remained largely underappreciated in the low-middle-income settings. The relatively higher disease burden, shorter life expectancy, and lower living standards in developing countries can be interpreted in terms of sociocultural and environmental determinants, such as age structure, gender disparities, low literacy rates, living environment, occupation and economic freedom, and the values and norms that guide peoples' beliefs and behaviour (Agorastos et al 2014;Galavotti and Schnell 1994;Tsai et al 2017; Development Impact Guest Blogger 2016; Decker and Constantine 2011; Gooneratne and Vitiello 2014). For instance, individuals with a higher socioeconomic status are more likely to be able to afford better housing, lead a healthy lifestyle, and enjoy higher quality of health and life compared to those in the lower socioeconomic strata (Zarini et al 2014;Bishwajit et al 2017; Amo-Adjei and Kumi-Kyereme 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the two constructs have remained largely underappreciated in the low-middle-income settings. The relatively higher disease burden, shorter life expectancy, and lower living standards in developing countries can be interpreted in terms of sociocultural and environmental determinants, such as age structure, gender disparities, low literacy rates, living environment, occupation and economic freedom, and the values and norms that guide peoples' beliefs and behaviour (Agorastos et al 2014;Galavotti and Schnell 1994;Tsai et al 2017; Development Impact Guest Blogger 2016; Decker and Constantine 2011; Gooneratne and Vitiello 2014). For instance, individuals with a higher socioeconomic status are more likely to be able to afford better housing, lead a healthy lifestyle, and enjoy higher quality of health and life compared to those in the lower socioeconomic strata (Zarini et al 2014;Bishwajit et al 2017; Amo-Adjei and Kumi-Kyereme 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Our national-and individual-level controls for whether women view intimate partner violence as acceptable are subject to the same limitations. Research has found that contextual information significantly impacts how women answer these questions (Tsai et al 2017), as does survey design (Yount et al 2011). In particular, DHS questions have been found to underrepresent the proportions of people who condone IPV (Schuler, Lenzi, and Yount 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Violence was, however, acceptable in some situations – such as infidelity - which might be interpreted differently depending on the perspectives of perpetrator and survivor. Recent evidence suggests that this loophole might be wider if transgression is perceived to be intentional rather than unintentional 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Responses to survey questions on gender norms – such as those used in Demographic and Health Surveys – may differ from responses to more contextualised questions based on illustrative vignettes 32 . Over three months in 2016, we held a series of focus group discussions and individual interviews.…”
Section: Methodsmentioning
confidence: 99%